EFFECT OF CHRYSOMYA DOMINATION ON CALCULATING POST MORTEM INTERVAL - Kristanto, Erwin G; Sembel, Dantje T; Salaki, Christina L; Kairupan, Carla; Huijbregts, Hans (Jurnal Biomedik : JBM, 2012)
Abstrak. Perkiraan saat kematian dihitung melalui penelitian dengan empat ekor bangkai hewan coba babi domestik pada lapangan terbuka dan area bersemak di Manado, Indonesia. Proses dekomposisi mulai dari tahap segar sampai skeletonisasi berlangsung selama 7-11 hari dengan tahap-tahap tumpang tindih, yang berbeda dengan di daerah empat musim (temperate). Chrysomya rufifacies dan Chrysomya megacepahala merupakan jenis lalat primer dominan yang ditangkap dari sekitar bangkai hewan coba dan dari hasil rearing. Simpulan: pada bangkai hewan coba yang didominasi oleh Chrysomya rufifacies dan Chrysomya megacephala, perkiraan saat kematian dengan menggunakan kedua spesies ini merupakan alat ukur terpercaya. Karakteristik perkembangan serangga amat dibutuhkan sebagai alat analitik untuk kepentingan penegakan hukum di Indonesia. Kata kunci: Chrysomya rufifacies, Chrysomya megacephala, dominasi, post mortem interval Â Abstract. Post mortem intervals (PMIs) were estimated in each of four decomposing pig carcasses located in an open field, as well as in a bushy area in Manado, Indonesia. The decomposition in Manado, proceeded from fresh to complete skeletonization, which occured within seven to eleven days, and lacked the intermediate step characteristics of decomposition as would be found in more temperate climates. Chrysomya rufifacies and Chrysomya megacepahala were the most dominant fly species collected near the carcasses, and from the rearing. Conclusion: estimation of PMIs in carcasses dominated by Chrysomya rufifacies and Chrysomya megacephala is best done by using the two spesies as measuring tools. Detailed characterization of the development of forensically important species across an array of conditions is necessary to provide adequate analytical tools for law enforcement agencies in Indonesia.Key words: Chrysomya rufifacies, Chrysomya megacephala, domination, post mortem interval